Development of Practical Tools Using Computer Power Supply for Light Vehicle Electrical System Learning - Aziz, Abdul; Khumaedi, Muhammad; Anis, Samsudin; Supraptono, Eko (Journal of Vocational and Career Education, 2025)
A common issue in the practical learning of light vehicle electrical systems is the inadequate availability of voltage sources, particularly batteries, in terms of quality and quantity. As a result, most students, after being assessed, receive scores that do not meet expectations. To address this issue, an alternative voltage source is needed to replace the battery, ensuring that the practical learning process for the light vehicle electrical system runs smoothly. This study aims to develop a practical tool using a computer power supply to improve the learning outcomes of the light vehicle electrical system. The research employs the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The experimental method used involves a pretest and posttest group, comparing the experimental class and the control class, consisting of 72 students. The results show that the practical tool using a computer power supply has a significant impact on the learning outcomes of the light vehicle electrical system, as analyzed through a one-tailed t-test. Based on N-Gain Score calculations, the tool is effective in improving learning outcomes, achieving high-level results. The conclusion of this research is that the practical tool using a computer power supply can replace the role of a battery as a voltage source in light vehicle electrical system practices.